Resting Frontal Eeg Asymmetry and Personality Traits: A Meta–Analysis. Issue 2 (March 2019) - Kuper, Niclas; Käckenmester, Wiebke; Wacker, Jan
Frontal asymmetry has been widely used as a marker of emotion, motivation, and psychopathology. When assessed during the resting state, it is regarded as an index of trait approach and withdrawal motivation. However, the replicability of these associations with personality is currently unclear. The present meta–analysis seeks to provide a comprehensive quantitative review of the relationship between personality traits and resting electroencephalographic (EEG) frontal asymmetry. We distinguished five personality clusters: extraversion, neuroticism, impulsivity, anger, and defensiveness. Data from 79 independent samples with overall 5700 participants were included in the meta–analysis. The results revealed that less than 0.4% of the variance in extraversion and neuroticism could be explained by resting frontal asymmetry. Similarly, a small effect was observed for trait anger, and a small–sized to medium–sized effect was observed for defensiveness, although the number of studies was very low. No significant effect emerged for impulsivity. The effects were further reduced after adjustment for publication bias. Given some evidence for heterogeneity, sub–traits were analysed, and methodological moderators were investigated. Based on the results, we conclude that the validity of resting frontal asymmetry as a marker for personality is not supported. Finally, recommendations are given to increase the replicability of frontal asymmetry research. © 2019 European Association of Personality Psychology